Children Activity Center Fasilitas Edukasi Berbasis Alam di Surakarta - Fardani, Kartika Juni, Dr. Ir. Dhani Mutiari, MT, Ir. Nurhasan, MT (2015)
In modern emancipation era the married women also can participate to work as a career woman. As a result, the time spends for child care is less. Another alternative is more the parents send their child to join a play group school or daycare. The Indonesian education profile still using centric characteristics basis as for continuing education school and do not have sense for sustainable on future live. The learning and development system that have been used as conventional learning system is not suitable with current conditions for quick developing in the science and technology. Teachers are also required to educate the student with to incorporate moral value, noble character, creativity, independence and leadership which is very hard to acceptance in the conventional learning system. The natural school concept is one of alternative on education system that use nature as the main media on learning their students. On natural school concept, they are learning more and active where the students learning through experience and observations. With direct learning the children or students are expected to learn to be more excited, do not get bored, and more creative. Other than getting a good education, the children also need to play while recreation that can develop the talents and creativity. At Surakarta it is no integrated place or institution for children to get education, to explore of talents and creativity, and the separation of children recreation area still making it difficult for the mobility of older people. Due to the separation of these areas, led the idea to design a place that can hold all activities in one area it is called Children Activities Center. Children Activity Center is a natural school concept facility in Surakarta with major activities such as child care, education, recreation, socialization and explore of talent and creativity that can support the children growth, both on physically and mentally with an alternate approach based nature. The main platform of activity is focused on early childhood education, namely 3-6 years while care activities intended for children aged 1 to 2 years.